TAT Kappa (TATK) : a novel cell penetrating peptide for delivery of pluripotent proteins into target cells - Ubashini Vijakumaran; Fazlina Nordin; Zariyantey Abd Hamid; Maha Abdullah; Gee, Jun Tye (Penerbit Universiti Kebangsaan Malaysia, 2022)
Induced pluripotent stem cell (iPSC) holds a magnificent place in the medical revolution. Its emergence is expected to instigate development of novel therapies for regenerative medicine and treatment of malignant diseases. Moreover, iPSC usage also resolved a long-time ethical controversy on the usage of the embryo as a pluripotent stem cells source. Since Yamanaka’s iPSC discovery in 2006, several pieces of research have proven that the enforced expression of transcription factors Oct-3/4, KLF4, and Sox2 can induce the reprogramming of previously differentiated cells, to generate iPSC. However, the conventional method using viral vectors leads to genetic modification due to exogene integration and subsequently tumorigenicity, which is unsafe for clinical application. Therefore, our study utilised an improved novel protein transduction domain, trans-activator of transcription kappa (TAT), a synthetic TAT-HIV to deliver these transcription factors gene as an alternative method for iPSC generation via non-viral reprogramming. With this new strategy, we have established a stable clone of 293T cells expressing TATκ fusion proteins (TATκ-GFP, TATκ-KLF4, TATκ-Sox2, and TATκ-Oct-3/4) that expresses and secretes their respective cloned reprogramming proteins. These stable clones successfully transduced our target cell (U937) monocyte cell line. TATκ-GFP, a marker protein and fusion proteins TATκ-KLF4, TATκ-Sox2, and TATκ-Oct-3/4 transduced the targeted (U937) monocyte cell line, proving that this novel TATκ possesses an ability to translocate across the cell membrane. Morphological changes were successfully observed in U937 cells after 20 days of transduction, however the presence of bonifide iPSC colonies were unable to be elicited. This might be due to the incomplete reprogramming or insufficient duration of protein transduction to generate iPSC cells.